FINANCIAL EVALUATION OF NAIMI SHEEP FATTENING SYSTEMS IN AL-AHSA GOVERNORATE, KINGDOM OF SAUDI ARABIA - & et al., Ameen (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This research was aimed at conducting a financial evaluation of sheep feeding systems in Al-Ahsa in KSA to identify the feasibility of investing in these projects. By field study, identified two systems for fattening the first system of fattening for 4 months, 3 cycles a year, and the second system of fattening for 6 months, two cycles a year. Secondary data collected by the Ministry of Environment, Water and Agriculture, the annual statistical book, a random sample of sheep breeders in Al-Ahsa governorate. The criteria for financial evaluation of projects are used. The results showed that the system of fattening for 4 months better than the other system, where the internal rate of return (IRR) for the first system 84% compared to 62% for the second, respectively. While the ratio of revenues to the cost of the two systems amounted to about 1.27, while the net present value amounted to 2592, 2160.7 thousand riyals respectively. In the absence of support, the preference of the fattening system are also shown for 4 months, with an internal rate of return of about 44% compared to 34% for the fattening system for 6 months. The study recommends directing the largest amount of Saudi investment to agricultural investment, particularly in the field of animal production, and encouraging investment in red meat manufacturing, to reduce reliance on imports from unsafe external sources and to achieve an appropriate level of food security in red meat.